The Sultanate of Delhi ( 1206-1526) : - Aniruddha Ray
This book provides an integrated view of the Delhi Sultanate government from 1206 to 1526. It is divided into two parts. The first part deals with the political events and the dynastic history of the Sultans and the second part with the administration, different land issues, social life including two major religious movements and other cultural aspects including architecture and sculpture. The growth of the city of Delhi has been shown here perhaps for the first time. Most of the books on Delhi Sultanate mainly narrate the political events. Here other aspects have been included to show the real character of the Sultanate. It may be mentioned that the English officials from the end of the eighteenth Century had termed the medieval period of India as a ‘dark age’ – a statement that has been accepted by several Indian writers. It is to negate this view that an integrated narrative has been provided here.